(untitled) (Chittagong University Journal of Biological Sciences, 2025)
Tomato (Lycopersicon esculentum (L.) Mill) is globally valued for its nutritional and health-promoting properties, particularly its protein and lycopene content. However, soil fertility declines and excessive dependence on inorganic fertilizers threaten both yield and fruit quality. Poultry manure biogas residue (PMBR), a stabilized organic amendment, offers a sustainable alternative, though its biochemical effects on tomatoes are not well understood. A field experiment was conducted at the University of Chittagong, Bangladesh, using a randomized complete block design with six treatments and three replicates, assessed the impact of PMBR, NPK, and their combinations on biochemical constituents (protein and lycopene) and nutritional quality of tomato. Sole PMBR (20 t ha⁻¹) markedly improved fruit quality, increasing protein by 57% (11.92 vs. 7.58%) and lycopene by 118% (52.03 vs. 23.82 mg kg⁻¹) over the control. Integrated treatments produced intermediate values, with decreasing PMBR and increasing NPK ratios, reducing protein and lycopene relative to sole PMBR. PMBR enhanced N, P, and Fe concentrations, indicating its potential for sustainable fertility management, improved tomato nutrition, and reduced chemical fertilizer dependence. Chittagong Univ. J. B. Sci. Vol. 13 (1&2): 60-67, 2025